The prevalence and correlates of physical inactivity among adults in Ho Chi Minh City - Trinh, Oanh TH (BioMed Central, 2008)
BACKGROUND: Socioeconomic changes have led to profound changes in individuals' lifestyles, including the adoption of unhealthy food consumption patterns, prevalent tobacco use, alcohol abuse and physical inactivity, especially in large cities like Ho Chi Minh City (HCMC). The Stepwise Approach to Surveillance of Non-communicable Disease Risk Factors survey was conducted to identify physical activity patterns and factors associated with 'insufficient' levels of physical activity for health in adults in HCMC. METHODS: A cross-sectional survey was conducted in 2005 among 1906 adults aged 25–64 years using a probability proportional to size cluster sampling method to estimate the prevalence of non-communicable disease risk factors including physical inactivity. Data on socioeconomic status, health behaviours, and time spent in physical activity during work, commuting and leisure time were collected. Physical activity was measured using the validated Global Physical Activity Questionnaire (GPAQ). Responders were classified as 'sufficiently active' or 'insufficiently active' using the GPAQ protocol. Correlates of insufficient physical activity were identified using multivariable logistic regression. RESULTS: A high proportion of adults were physically inactive, with only 56.2% (95% CI = 52.1–60.4) aged 25–64 years in HCMC achieving the minimum recommendation of 'doing 30 minutes moderate-intensity physical activity for at least 5 days per week'. The main contributors to total physical activity among adults were from working and active commuting. Leisure-time physical activity represented a very small proportion (9.4%) of individuals' total activity level. Some differences in the pattern of physical activity between men and women were noted, with insufficient activity levels decreasing with age among women, but not among men. Physical inactivity was positively associated with high income (OR = 1.77, 95% CI = 1.05–2.97) and high household wealth index (OR = 1.86, 95% CI = 1.29–2.66) amongst men. CONCLUSION: Public health policies and programs to preserve active commuting in HCMC and to promote time spent in recreational physical activity in both genders and across all age groups, but especially among young adults, will be critical in any comprehensive national plan to tackle inactivity. Clear and consistent national recommendations about how much physical activity Vietnamese people need for preventing and managing non-communicable diseases should also be part of this population-wide promotional effort.